Thick layers liquid-phase epitaxy method - Dranchuk, S. N.; Zavadskiy, V. A.; Mokritskiy, V. A. (Technology and design in electronic equipment, 2013)
On the basis of the authors’ model of mass transfer, a new method for thick layers epitaxy has been developed. The method provides for the growth of different parts of the layers in two-layer systems obtained from the solution-melt and allows to control the thickness of substrate submelting and the thickness of layers obtained at the upper and lower substrates, in consideration of different crystallized substance transport mechanisms.